Religious Court Decisions Regarding the Revocation of Grant (Hibah) in the Perspective of Islamic Jurisprudence - Harahap, Purnama Hidayah; Asmuni; Syahputra, Akmaluddin; Meidina, Ahmad Rezy; Zein, Anwar (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
This scholarly article examines the judgments rendered by Religious Courts concerning disputes related to the revocation of grants, employing the viewpoint of Islamic jurisprudence and the maslahah theory. In this instance, the judicial panel overseeing the dispute related to the cancellation of the grant primarily invoked the provisions outlined in Article 35, Paragraph 1, and Article 36, Paragraph 1 of the Marriage Act (Law Number 1 of 1974), which pertain to joint property, along with Article 1338 of the Civil Code, addressing agreements. Consequently, the judges disregarded the article pertaining to the right to withdraw the grant’s subject, even though the grant is given without the consent of the other heirs. Meanwhile, in accordance with the maslahah theory, decisions rendered by a panel of judges in the Religious Court ideally aim to actualize the concept of Maqasid al-Shari’ah, specifically focused on the preservation of both property and descendants. This approach helps mitigate adverse consequences that may arise within familial dynamics, particularly in relationships between parents and their heirs. Nevertheless, in accordance with Hans Kelsen’s justice theory, the deliberations undertaken by judges when adjudicating cases involving the revocation of grants often exhibit inconsistency in the application of the pertinent legal framework, thereby leading to a partial realization of the intended concept of justice.